The influence of different abiotic conditions on the concentrations of free and conjugated deoxynivalenol and zearalenone in stored wheat - Oluwakayode, Abimbola; Greer, Brett; He, Qiqi; Sulyok, Michael; Meneely, Julie; Krska, Rudolf; Medina, Angel (Springer, 2024)
Environmental factors influence fungal growth and mycotoxin production in stored grains. However, the concentrations of free mycotoxins and their conjugates and how they are impacted by different interacting environment conditions have not been previously examined. The objectives of this study were to examine the impact of storage conditions (0.93–0.98 aw) and temperature (20–25 °C) on (a) the concentrations of deoxynivalenol and zearalenone and their respective glucosides/conjugates and (b) the concentrations of emerging mycotoxins in both naturally contaminated and irradiated wheat grains inoculated with Fusarium graminearum. Contaminated samples were analysed for multiple mycotoxins using Liquid Chromatography Tandem Mass Spectrometry (LC–MS/MS). Method validation was performed according to the acceptable performance criteria set and updated by the European Commission regulations No. 2021/808/EC. As an important conjugate of deoxynivalenol, the concentrations of deoxynivalenol-3-glucoside were significantly different from its precursor deoxynivalenol at 0.93 aw (22% moisture content- MC) at 25 °C in the naturally contaminated wheat with a ratio proportion of 56:44% respectively. The high concentrations of deoxynivalenol-3-glucoside could be influenced by the wheat’s variety and/or harvested season/fungal strain type/location. Zeralenone-14-sulfate concentrations were surprisingly three times higher than Zearalenone in the naturally contaminated wheat at 0.98 aw (26% MC) at both temperatures. Emerging mycotoxins such as moniliformin increased with temperature rise with the highest concentrations at 0.95 aw and 25 °C. These findings highlight the influence and importance of storage aw x temperature conditions on the relative presence of free vs conjugated mycotoxins which can have implications for food safety.
Keywords: Deoxynivalenol; Zearalenone; Conjugated mycotoxins; Water activity; LC–MS/MS